2015
DOI: 10.1093/ejcts/ezv296
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score-matching analysis of hybrid video-assisted thoracoscopic surgery and thoracoscopic lobectomy for clinical stage I lung cancer

Abstract: In this single-institution, propensity score-matched study, hybrid VATS showed a shorter operative time and similar outcomes compared with thoracoscopic lobectomy for clinical stage IA lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The hybrid VATS lobectomy uses both direct and video visualization, whereas thoracoscopic VATS lobectomy uses only video visualization. A propensity-matched analysis (11) of these methods showed that the former involves shorter operation times and no differences in bleeding, chest tube duration, or complications, as well as no significant differences in OS or DFS. In another study (12), only surgical time (better with muscle-sparing thoracotomy) and hospitalization time (better with VATS) were different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid VATS lobectomy uses both direct and video visualization, whereas thoracoscopic VATS lobectomy uses only video visualization. A propensity-matched analysis (11) of these methods showed that the former involves shorter operation times and no differences in bleeding, chest tube duration, or complications, as well as no significant differences in OS or DFS. In another study (12), only surgical time (better with muscle-sparing thoracotomy) and hospitalization time (better with VATS) were different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Their method seems to be reasonable with respect to the tumor surgical margin issue. Both hybrid VATS [44] and the muscle-sparing thoracotomy [45] approach have a shorter operative time and similar outcomes compared with thoracoscopic lobectomy.…”
Section: Vats Segmentectomymentioning
confidence: 99%
“…Elderly NSCLC patients treated with thoracic lobectomy have a postoperative mortality rate of 0 to 4.8% and a postoperative complication rate of 20-54% [9,10]. Since the rst videoassisted thoracoscopic (VATS) lobectomy was performed in 1992 [11], the continuous development of minimally invasive surgical techniques and instruments, accumulation of surgical experience, and continuous reports of good long-term survival in surgical patients [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] has prompted the NCCN guidelines to recommend VATS lobectomy as a surgical method for treatment of resectable NSCLC [28].…”
Section: Introductionmentioning
confidence: 99%